2014
DOI: 10.3389/fnagi.2014.00193
|View full text |Cite
|
Sign up to set email alerts
|

The neural architecture of age-related dual-task interferences

Abstract: In daily life elderly adults exhibit deficits when dual-tasking is involved. So far these deficits have been verified on a behavioral level in dual-tasking. Yet, the neuronal architecture of these deficits in aging still remains to be explored especially when late-middle aged individuals around 60 years of age are concerned. Neuroimaging studies in young participants concerning dual-tasking were, among others, related to activity in middle frontal (MFG) and superior frontal gyrus (SFG) and the anterior insula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 83 publications
0
11
1
Order By: Relevance
“…However, and most important, the covariate analysis showed that age had no impact on the observed effects in this study. In comparison to other studies of aging on dual tasking (e.g., Li et al, 2001 ; Verhaeghen et al, 2003 ; Verhaeghen, 2011 ; Beurskens and Bock, 2012 ; Chmielewski et al, 2014 ; Bier et al, 2017 ), the age differences as observed here were rather small. Other factors differing between controls and MS patients (e.g., BDI and MFIS) did also not bias the results of this study, as shown by the covariate analysis controlling for these factors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, and most important, the covariate analysis showed that age had no impact on the observed effects in this study. In comparison to other studies of aging on dual tasking (e.g., Li et al, 2001 ; Verhaeghen et al, 2003 ; Verhaeghen, 2011 ; Beurskens and Bock, 2012 ; Chmielewski et al, 2014 ; Bier et al, 2017 ), the age differences as observed here were rather small. Other factors differing between controls and MS patients (e.g., BDI and MFIS) did also not bias the results of this study, as shown by the covariate analysis controlling for these factors.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that dual-tasking conditions, where different cognitive processes related to the selection of actions have to be monitored in parallel, are very sensitive to even slight alterations in the functioning of neuronal networks ( Beste et al, 2013a ). The efficient usage of widely distributed functional networks including frontal, subcortical, parietal, and primary sensory regions are essential for performance in dual-tasking ( Dux et al, 2006 ; Marois et al, 2006 ; Szameitat et al, 2006 ; Stelzel et al, 2008 ; Chmielewski et al, 2014 ; Yildiz and Beste, 2014 ; Gohil et al, 2015 , 2017 ; Stock et al, 2017 ). Since MS may be described as a disease affecting the human “connectome” ( Griffa et al, 2013 ) and functional connectivity between brain areas is critically affected by microstructural lesions especially in white matter structures ( Bonzano et al, 2009 , 2011 ; Droby et al, 2016 ), dual-tasking processes may be of particular relevance and are very sensitive to detect early and subtle cognitive (executive) dysfunctions in MS. Additionally, it has been shown that dual-task performance is modulated by neurobiological systems ( Schulz et al, 2012 ; Beste et al, 2013b ; Yildiz et al, 2013 , 2014 ; Stock et al, 2014 ) that are either directly or indirectly affected in MS, like the dopaminergic system ( Pacheco et al, 2014 ; Dobryakova et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, our findings may represent an important first step in stimulating further research to assess whether videogames can be used to optimize cognitive control. Importantly, given the importance of action control in daily activities and the known difficulties shown by older adults in response selection and action cascading processes [ 82 , 87 89 ], our findings can have important practical implications for designing intervention/training studies aimed at overcoming or slowing down action control deficits associated with aging.…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, it has been suggested that age-related deficits in dual-task performance ( Lindenberger et al, 2000 ; Hartley, 2001 ; Verhaeghen and Cerella, 2002 ; Dubost et al, 2006 ; Göthe et al, 2007 ; Granacher et al, 2011 ) and corresponding changes in neural activation ( Hartley et al, 2011 ; Chmielewski et al, 2014 ) may result from an underlying WM dysfunction ( Awh et al, 2006 ; Gazzaley and Nobre, 2012 ).…”
Section: Introductionmentioning
confidence: 99%